Pengaruh Slack Resources, Green Accounting dan Public Ownership Terhadap Pengungkapan Corporate Social Responsibility : (Studi pada Sektor Consumer Non-Cyclicals yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2017-2022) - Agnes Sherine Septiara Malau; Willy Sri Yuliandhari (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
Corporate social responsibility (CSR) disclosures include information about the social activities a company undertakes to shape public perceptions of the company. These disclosures can also have a significant impact on a company's financial performance. The aim of this study is to investigate the effect of Slack Resources, Green Accounting, and Public Ownership on CSR disclosure. The subjects of this study are industrial issuers of the non-cyclical consumer segment listed in Bursa Efek Indonesia (BEI) during the period 2017 to 2022. The purposive sampling method was utilized to collect data which consisted of 8 companies over a 6-year period. Regression panel data analysis is utilized as the main method of analysis, with the help of E-views 12 software to process the data.